128k views
1 vote
Find the difference of functions s and r shown

below.
r(x) = -x2 + 3x
s(x) = 2x + 1
(s - r)(x) =

User GibboK
by
6.5k points

1 Answer

4 votes

Answer:


\displaystyle (s-r)(x) = x^2 - x + 1

Explanation:

We are given the two functions:


\displaystyle r(x) = -x^2 + 3x \text{ and } s(x) = 2x + 1

And we want to find:


\displaystyle (s-r)(x)

This is equivalent to:


\displaystyle (s-r)(x) = s(x) - r(x)

Substitute and simplify:


\displaystyle \begin{aligned}(s-r)(x) & = s(x) - r(x) \\ \\ & = (2x+1)-(-x^2+3x) \\ \\ & = (2x+1)+(x^2-3x) \\ \\ & = x^2 +(2x-3x) + 1 \\ \\ & = x^2 - x + 1 \end{aligned}

In conclusion:


\displaystyle (s-r)(x) = x^2 - x + 1

User Venkatareddy
by
5.5k points